Influence of social media on students’ academic achievement - Basil Chinecherem Oguguo; Juliet O. Ajuonuma; Roseline Azubuike; Catherine U. Ene; Florence O. Atta; Chidimma J. Oko (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study determined the influence of using social media on the academic achievement of senior secondary school students. A sample of 150 students comprising 70 males and 80 females were drawn from five schools and used for the study, this was arrived at through multi-stage sampling procedure. Social Media Questionnaire (SMQ) and Students’ Accounting Achievement Proforma (SAAP) were used for data collection. The result showed that students frequently engage in social media in order to make new friends, research about their assignments and source for other educational materials, stay up to dates with latest trends and news. The finding also showed that students spend an average, 2 to 4 hours daily on social media. There was no significant influence of frequency of social media use by students on their mean academic achievements in Accounting; however, gender of students was found to have a significant influence on students’ mean academic achievement in Accounting. Students should be guided properly and informed on the vulnerabilities likely to come their way if they fail to appropriately utilize the opportunities that come with having social media platforms.